The role of the Government in promoting Small and Medium-Sized Enterprises (SMEs) in Bangkok Metropolitan Area - Yamoutai, Thundthornthep; Siriphornwut, Nattawat (Journal of Management Science Nakhon Pathom Rajabhat University, 2025)
The research aimed to 1) study the role of the government in promoting SMEs in Bangkok Metropolitan Area, 2) study the need for support from the government for SME entrepreneurs in Bangkok Metropolitan Area, and 3) propose guidelines for strengthening the role of the government in business law in promoting SMEs in Bangkok Metropolitan Area. The research method was qualitative. There were 20 key informants, divided into four groups: SME entrepreneurs, representatives from financial institutions, representatives from government agencies and state enterprises related to promoting SMEs, and academics or experts in SMEs. In-depth interviews were conducted face-to-face using a semi-structured interview form, and data were analyzed by coding. The research results found that 1) the role of the government in promoting SMEs was the heart of national economic development. Although there were many government policies and measures, they remained difficult to access, lacked clarity, and did not include proper follow-up and evaluation. Therefore, the results were not as effective as they should have been. “I didn’t even know where to follow up. I only knew that there were banks that provided loans for investment.” 2) The need for support from the government was divided into three main dimensions: potential development “If the government could be a consultant or provide a mentor system, it would be great because it wasn’t just about organizing training and then ending it. There had to be continuous monitoring and evaluation.” In terms of marketing and sales “If possible, I would have liked the government to help open clearer sales channels and increase market access.” And in terms of finance “I felt that the system was still not supportive enough for SMEs.” 3) The approach to strengthening the role of the government was to integrate cooperation and coordination between government agencies, the private sector, and financial institutions (banks) in promoting SMEs, including developing an ecosystem and support measures that met the needs of entrepreneurs. Article history: Received 19 March 2024 Revised 12 June 2025 Accepted 19 June 2025 SIMILARITY INDEX = 9.72 %